P036 Predictors of lost to follow-up in a 'test and treat' programme among women with high-risk sexual behaviour in kampala, uganda. (14th July 2019) - Kamacooko, Onesmus; Mayanja, Yunia; Bagiire, Daniel; Namale, Gertrude; Seeley, Janet
Abstract : Background: Immediate uptake of antiretroviral therapy (ART) after an HIV-positive diagnosis (Test and Treat) is now being implemented in Uganda. Data are limited on lost to follow-up (LTFU) in high-risk cohorts that have initiated 'Test and Treat'. We describe LTFU in a cohort of women of high-risk sexual behaviour who initiated ART under 'Test and Treat'. Methods: We performed a retrospective cohort study of participant records at the Good Health for Women Project (GHWP) clinic, a clinic in Kampala for women at high-risk of HIV-infection. We included HIV positive women ≥ 18 years who initiated ART at GHWP between August 2014 and October 2017. We defined LTFU as not taking an ART refill for ≥3 months from the last clinic appointment and not classified as dead or transferred to another clinic. We used the Kaplan-Meier technique to estimate time to LTFU after ART initiation. Predictors of LTFU were assessed using a multivariable Cox proportional hazards model. Results: Of the 293 enrolled participants, 16% of the women were LTFU within the first year of ART initiation. The mean (±SD) age of study participants was 30.3 (± 6.5) years, with 274(94%) reporting paid sex while 38(13%) had never tested for HIV before enrolment into GHWP. LTFU in the cohort was estimated at 12.5 per 100 person-years (95%CI 9.8–16.0). In multivariable analysis, participants who reported sex work as their main job at ART initiation (Adjusted Hazards Ratio [aHR] =1.98, 95%CI 1.12–3.52), having baseline WHO clinical stage III or IV (aHR= 2.65, 95% CI 1.26–5.60) were more likely to be LTFU. Conclusion: LTFU in this cohort is high. Follow up strategies are required to support women on Test and Treat to remain on treatment, especially those who engage in sex work and those who initiate ART at a later stage of disease. Disclosure: No significant relationships.